Healthcare services utilisation among patients with hypertension and diabetes in rural Ghana - Opare-Addo, Mercy N.A. (Afr J Prim Health Care Fam Med, 2020)
BACKGROUND: Non-communicable diseases (NCDs) remain a global burden and is projected to increase due to aging, rapid urbanization and unhealthy lifestyles. The study was conducted to determine the prevalence of hypertension and diabetes in rural districts in the Ashanti region of Ghana and to determine factors that influence utilization of health care services. SETTING: Offinso North, Amansie West, Ahafo Ano South, and Asante Akim South. METHODS: A population based prospective cross-sectional study comprising of adults aged 18 years and above was carried out from January 2016 to March 2016. A multistage sampling method was employed to select four rural districts in the Ashanti region of Ghana. A structured questionnaire was used to collect primary data from respondents. RESULTS: A total of 684 participants were recruited in the study. The prevalence of hypertension and diabetes was found to be 16.23% and 5.41% respectively. The prevalence of diabetes and hypertension comorbidity was 1.61%. The public hospital was the most preferred choice of facility (52.56%) for patients with NCDs. Educational level significantly decreased the likelihood of seeking healthcare in OTCMS and Health Centre to Hospitals (RRR = 0.1, 95% CI = 0.011–0.917, p = 0.042) and (RRR = 0.4, 95% CI = 0.198-0.679, p = 0.001) respectively. CONCLUSION: The prevalence of self -reported hypertension and diabetes observed in this study was relatively lower for hypertension and higher for diabetes as compared to other studies in Ghana. The public hospital is the most preferred choice of health facilities for patients with hypertension and diabetes in the rural districts.